The effect of SAQ training to increase the agility of badminton atheletes aged 12-13 years - Marom, Muhammad Faisal; Darmawan, Arief; Fitriady, Gema (STKIP PGRI Jombang, 2023)
This study aims to determine the effect of the SAQ training program on increasing the agility of PB badminton athletes. Bendo Sport aged 13-15 years. The athlete sampling technique used was a total sampling of 15 male athletes. The research instrument that researchers used in this study was the Illinois Agility Test. The research method used by researchers is one group pretest-post test design. The results of calculating the data from the pretest and posttest obtained the following results, the mean pretest was 17.44 ± 0.59 and the post test was 16.34 ± 0.52. In subsequent calculations, a significance value of <0.001 was obtained. It could be concluded that there were differences before training and after training.